Intramuscular injections of iron compounds and oncogenesis in man. Issue 6114 (18th March 1978) - Weinbren, K; Salm, R; Greenberg, G
Abstract : To evaluate the evidence for iron compounds as local carcinogens in man, histological material and clinical reports have been reviewed in seven of the eight published cases of tumours developing at the site of intramuscular injections. The microscopical appearances suggested benign lesions in two cases and a variety of tumours in the other five. In only two cases (a rhabdomyosarcoma and a fibrosarcoma) was the interval between injections and tumour development longer than six years. Of the remaining three tumours, one was considered to be a rather slowly growing haemangiopericytoma (with an interval of two years), one appeared to be a subcutaneous lymphoma with no evidence of having arisen in the gluteal muscles, and one was a pleomorphic sarcoma with a possible five-year interval. Sarcomas induced experimentally by iron compounds differ in being less variable in type and in containing abundant iron-containing macrophages, which were negligible in these human tumours. Although the total number of patients who have received intramuscular injections of iron compounds is not known, the present findings, in contrast to experimental work, do not support the view that such treatment carries a strong risk of tumour development.